The A Allele of the rs1990760 Polymorphism in the IFIH1 Gene Is Associated with Protection for Arterial Hypertension in Type 1 Diabetic Patients and with Expression of This Gene in Human Mononuclear Cells - Bouças, Ana P. (Public Library of Science, 2013)
BACKGROUND: The rs1990760 polymorphism of interferon induced with helicase C domain 1 (IFIH1) has been associated with type 1 diabetes mellitus (T1DM). Here, we investigated whether this polymorphism is associated with T1DM or its clinical characteristics in a Brazilian population, and if IFIH1 gene expression in mononuclear cells from T1DM patients differs according to the genotypes of this polymorphism. A meta-analysis was also conducted to evaluate if the rs1990760 polymorphism is associated with T1DM. METHODS: Frequencies of the rs1990760 polymorphism were analyzed in 527 T1DM patients and in 517 healthy subjects. IFIH1 gene expressions according to genotypes were measured in a sub-sample of 26 T1DM patients by quantitative real-time PCR. RESULTS: Our data show the association of the A allele with risk to T1DM under a dominant model of inheritance [odds ratio (OR) = 1.421, P = 0.037], adjusting for ethnicity. The meta-analysis revealed significant association between the rs199760A allele and risk for T1DM for all analyzed inheritance models. Surprisingly, T1DM patients carrying the A allele showed lower levels of systolic (P = 0.001) and diastolic (P = 1×10(−10)) blood pressures as compared to G/G carriers. Furthermore, the A/A genotype seems to be associated with protection to arterial hypertension (AH) after adjustment for covariates (OR = 0.339, P = 0.019). IFIH1 gene expression in mononuclear cells from 26 T1DM patients did not differ among genotypes (P = 0.274). Nevertheless, IFIH1 gene expression was increased in mononuclear cells from T1DM patients with AH as compared with T1DM patients without AH [6.7 (1.7–2.0) vs. 1.8 (1.3–7.1) arbitrary units; P = 0.036]. The association with blood pressures and AH was not observed in patients with type 2 diabetes mellitus. CONCLUSIONS: Our results indicate that the rs1990760 polymorphism is associated with T1DM. Interestingly, the rs1990760 A allele seems to be associated with protection for AH in T1DM patients. Further studies are needed to confirm the association with AH.